‘In an otherwise limitless world, I was sure of my limit.’† Experiencing Anorexia Nervosa: A phenomenological metasynthesis - Bryant, Emma; Aouad, Phillip; Hambleton, Ashlea; Touyz, Stephen; Maguire, Sarah (Frontiers in Psychiatry, 2022)
Anorexia Nervosa (AN) has the highest mortality rate of the mental disorders, with still less than 50% of affected individuals achieving recovery. Recent calls to bring innovative, empirical research strategies to the understanding of illness and its core psychopathological features highlight the need to address significant paucity of efficacious treatment. The current study brings a phenomenological approach to this challenge, synthesising lived experience phenomena as described by qualitative literature. Fifty-three studies published between the years 1998 and 2021 comprising a total of 1557 participants aged 12-66 suffering from AN or sub-threshold AN are included. Reciprocal and refutational analysis generated six key third-order constructs: “emotion experienced as overwhelming”, “identity”, “AN as a tool”, “internal conflict relating to Anorexia”, “interpersonal communication difficulties” and “corporeality”. Twenty-six sub-themes were identified, the most common being fear, avoidance, AN as guardian/protector, and AN as intertwined with identity. Some themes associated with current treatment models such as low self-esteem, need for social approval and feelings of fatness were less common. We highlight the significant role of intense and confusing emotion in AN, which is both rooted in and engenders amplified fear and anxiety. Restrictive eating functions to numb these feelings and withdraw an individual from a chaotic and threatening world whilst providing a sense of self around which to build an illness identity. Results have implications for therapeutic practice and overly protective weight and shape focused medical treatment models, which may serve to reinforce the disease.